Suppressive Activity of a Macrolide Antibiotic, Roxithromycin, on Pro-Inflammatory Cytokine Production in Vitro and in Vivo - H. Suzaki; K. Asano; S. Ohki; K. Kanai; T. Mizutani; T. Hisamitsu (Mediators of Inflammation)
This study was designed to examine the influence of a macrolide antibiotic, roxithromycin (RXM), on the production of pro-inflammatory cytokines, interleukin (IL)-1β and tumor necrosis factor (TNF)-α. In the first experiments, we examined the effect of RXM on in vitro cytokine production from lipopolysaccharide (LPS)-stimulated human peripheral blood monocytes. The monocytes were cultured in the presence of various doses of the agent. After 24 h, the culture supernatants were obtained and assayed for IL-1β and TNF-α contents by enzyme-linked immunosorbent assay. RXM suppressed the in vitro production of IL-1β and TNF-α in response to LPS stimulation. This was dose dependent and first noted at a concentration of as little as 0.05 μg/ml, which is much lower than therapeutic blood levels. In the second part of the experiments, we examined the influence of RXM on the appearance of IL-1β and TNF-α in mouse lung extract induced by LPS inhalation. RXM was administered orally into BALB/c mice at a single dose of 2.5 mg/kg once a day for 5-12 weeks. These mice were then instilled with LPS into the trachea and examined for the presence of cytokines in aqueous lung extracts. Pretreatment of mice with RXM for 5 weeks did not influence of the appearance of both IL-1β and TNF-α in aqueous lung extracts. However, pretreatment for more than 7 weeks dramatically suppressed the cytokine appearance in the extracts.